PERBANDINGAN TINGKAT PENGETAHUAN PETANI SEBELUM DAN SESUDAH MENGGUNAKAN MEDIA VISUAL DAN MEDIA AUDIO-VISUAL TERHADAP PETANI DI KELURAHAN TELAGA SAMSAM KECAMATAN KANDIS KABUPATEN SIAK - Resti Yulanda Sari; Roza Yulida; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research is aimed to determine are: 1) First knowledge of the farmers in extension of kencana’s chili cultivation technique; 2) The level farmer’s knowledge before-after using visual and audio-visual media. This research was conducted inTelaga Samsam Sub-district Kandis district Siak Regency. This research is experiment trait by taking sample is census as many were 30 respondents. Analyze data were using of this research are Skala Likerts Summated Rating Scale (LSRS ) and Paired Sample Test. The result showed that the first knowledge of the farmers in extension of kencana’s chili cultivation is “quite knowing “with the score 2,79. Based on data Paired Sample Test analysis that the use of visual media before (mean=1,964 ) and visual media after (mean =2, 6553 by supported are t-hitung -3.268 and Sig 2 tailed .003<0,05 it means there are difference significant of level farmer’s knowledge in extension of kencana’s chili cultivation technique before-after using visual media, not difference way with the audio-visual media, the data analyze showed that the use of audio-visual before (mean=1,9640 ) and audio-visual after (mean =2,7I82) by supported are t-hitung -8.662 and Sig 2 tailed .000<0,05 it means there are very difference significantly of level farmer’s knowledge in extension of kencana’s chili cultivation technique before-after using audio-visual. Keywords: Comparison, Level of Farmer’s Knowledge, Visual and Audio-Visual Media